Digital signature method and device, storage medium and electronic equipment - ZHONG JI; HAN FANGZHEN (2025)
The embodiment of the invention provides a digital signature method and device, a storage medium and electronic equipment, and the method comprises the steps: carrying out the discretization of a to-be-signed target message, and obtaining N sub-messages, N being an integer greater than 1; processing each sub-message through the initialized parameter set to obtain a Hamming weight of each sub-message; and signing each sub-message by using the Hamming weight to obtain N signature results of the N sub-messages, and determining the N signature results as a target signature result of the target message. According to the invention, the method solves a problem that the signature of an elliptic curve cryptographic algorithm in the prior art consumes much time. 本申请实施例提供了一种数字签名方法及装置、存储介质和电子设备，其中，该方法包括：对待签名的目标消息进行离散化得到N个子消息，N是大于1的整数；通过初始化的参数集合对各个子消息进行处理得到各个子消息的汉明权重；使用汉明权重对各个子消息进行签名，得到N个子消息的N个签名结果，并将N个签名结果确定为目标消息的目标签名结果。通过本申请，解决了相关技术中椭圆曲线密码算法的签名耗时较多的问题。